The Role of Geography in Urban Spatial Planning - Lasaiba, Mohammad Amin; Sihasale, Daniel Anthoni (Universitas Pattimura, 2022)
The rapid and complex development of cities has impacted various aspects of people's lives, including environmental, social, economic, and political issues. Therefore, spatial planning is essential in maintaining sustainable urban development. Geography is crucial in determining optimal spatial patterns, identifying and analyzing urban area issues, and providing solutions and recommendations to overcome them. In spatial planning, geography also utilizes GIS (Geographic Information System) technology to map and analyze spatial data visually, which can assist in decision-making and more effective and efficient development planning. In this regard, the role of geography is critical to understanding and identifying these issues and providing appropriate and sustainable solutions. In conclusion, geography has a significant role in urban spatial planning. It can assist in determining optimal spatial patterns, identifying and analyzing urban area issues, and providing appropriate and sustainable solutions and recommendations..